Electrocardiography vs. Auscultation to Assess Heart Rate During Cardiac Arrest With Pulseless Electrical Activity in Newborn Infants - Luong, Deandra H.; Cheung, Po-Yin; O'Reilly, Megan; Lee, Tze-Fun; Schmolzer, Georg M. (Frontiers in Pediatrics, 2018)
Background In 2015, the neonatal resuscitation guidelines incorporated the use of electrocardiography (ECG) to monitor heartrate of newborns. However, previous studies have indicated that cardiac arrest with pulseless electrical activity rhythm (PEA) may occur in the delivery room, rendering this method problematic. Objectives To evaluate the accuracy of ECG and auscultation to assess heart rate during PEA. Methods A total of 45 piglets (age 1-3days, weight 1.7-2.3kg) were exposed to 30min normocapnic alveolar hypoxia followed by asphyxia until asystole, achieved by disconnecting the ventilator and clamping the endotracheal tube. During asphyxia, heart rate (HR) was assess using auscultation, ECG, and carotid blood flow (CBF). At the time of asystole (defined as zero CBF) HR auscultated using a neonatal/infant stethoscope was compared to ECG traces. Results The median (IQR) duration of asphyxia was 325 (200-491) sec. In 8 (18%) piglets, CBF, ECG, and auscultation identified asystole. In 22 (49%) piglets no CBF and no audible heart sounds, were observed, while ECG displayed a HR ranging from 17-75/min. Fifteen (33%) piglets remained bradycardic (defined as HR of <100/min) after 10min of asphyxia, which was identified by CBF, ECG, and auscultation. The overall accuracy of ECG and auscultation in the detection of HR were 51% and 80%, respectively (p=0.004). Conclusion In cases with PEA ECG is not superior in correctly identifying HR in newborn piglets.